Coordinated control and power management of diesel-PV-battery in hybrid stand-alone microgrid system - Xiao-Peng Ji; Qian-Jie Liu; Qian-Jie Liu; Zhao Liu; Yun-Yun Xie; Jiang-Tao Zhai (The Journal of Engineering, 2019)
Coordinated control and power management of distributed energy resources, such as diesel generators (DGs), photovoltaics (PVs) and battery energy storage systems (BESSs), is vital for secure, reliable and economical operation of a stand-alone microgrid system. This paper proposes a coordinated control and power management approach for a hybrid stand-alone microgrid system containing DGs and PVs and also BESSs, which commonly servers as a power supply solution for remote areas such as islands. The proposed approach takes into account the maximum utilisation of PV power, economical operation condition of diesel generators, status of battery energy storage system and their operation constraints to share the load among them. Efficacy of the proposed approach is validated through a RTDS-based simulation test and an actual project practice.